2015
DOI: 10.1007/s00345-015-1694-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus conventional laparoscopic pyeloplasty in children less than 20 kg by weight: single-center experience

Abstract: This comparative study confirms the feasibility, efficacy, and safety of robotic pyeloplasty in infants and toddlers. The obvious advantage is being shorter hospital stay. Further prospective studies will be needed to show its superiority over LP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
(10 reference statements)
1
22
0
Order By: Relevance
“…All 17 were observational studies . Thirteen studies had a retrospective design [], three were prospective , and one used both retrospective and prospective data collection . Two studies reported patient matching .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 17 were observational studies . Thirteen studies had a retrospective design [], three were prospective , and one used both retrospective and prospective data collection . Two studies reported patient matching .…”
Section: Resultsmentioning
confidence: 99%
“…). Ten studies reported similar complication rates between approaches []. Four studies reported complication rates of 0% for both groups .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports indicated that RP achieved a similar success rate, shorter hospital stay, and lower narcotic usage compared to OP (31)(32)(33)(34)(35)(36)(37). Additionally, RP and LP were shown to be effective techniques for treating UPJO, with similar success rates (21,(38)(39)(40)(41)(42). Compared to LP, RP had a shorter operative time in several reports ( Table 2) (21,39,41), possibly because of the shorter intracorporeal suturing time.…”
Section: Pyeloplastymentioning
confidence: 99%